Holoprosencephaly from conception to adulthood. Issue 2 (24th July 2018) - Weiss, Karin; Kruszka, Paul S.; Levey, Eric; Muenke, Max
Abstract : Holoprosencephaly (HPE) consists of a spectrum of malformations related to incomplete separation of the prosencephalon. There is a wide clinical variability depending on the HPE subtype seen on imaging. Early postnatal lethality is common, however a significant fraction of newborns diagnosed with HPE will survive into childhood and even adulthood. Here we will review the clinical management of HPE during different ages from the prenatal period to adulthood.